A educação em direitos humanos na educação básica: a presença da EDH no Colégio Marista Pio X - Cavalcante, Wallene de Oliveira (2015)
This research's mais goal is to analyze the normatives policies that guide the Education in Human Rights on the Global, National and Regional Plan, as well as its application in the scope of Basic Education in Marista Network of Education, and how it has been worked by the teachers and the Education in Human Rights as a curricular component in Marista Pio X School. As the specific goals, it was sought to understand the fundamental aspects of Marista Network of Basic Education's history and the process of forming the Marista Institute in France and its coming to Brazil, to learn the educational-historic context of Marista Institute with the human rights actions and to investigate the associated elements to pedagogical and curricular practice of Education in Human Rights subject in Marista Pio X School. To achieve this aim, a timeline was built following the international standards, reaching the Education in Human Rights policy in Brazil. Categories of historic-educational analysis of space/time ("scholarly architecture ", territory, place, simbology), curriculum (Giroux), viable unprecendent and emancipation (Freire), transdisciplinarity (Morin) and the interculturality (Candau) were used. In this context are located the oficial documents of Marista Institute and Marista Union of Brasil - UMBRASIL, specially the Educational Project of Marista Brazil and Marista Curricular Matrix, both from 2010, important references for including Education in Human Rights as a curricular subject in Marista Network of Basic Education, reaching the central matter of this research, with a bibliographic -documental character, when the experience of EDH in Marista Pio X School will be analyzed , in João Pessoa (PB), taught at 9th grade of Fundamental School since 2012. From the propositions raised, some hypotheses were formulated: the founding documents of Marista Institute demonstrate the commitment with the defense of education right as a fundamental human right; the pedagogical and management actions developed in the scope of Marista Pio X School, before legal standards of EDH, are already present conceptions and practices substantiated in Human Rights that estimulate the citizen participation of persons under law. The relevance of the theme proposed is justified before the urgency of educating in human rights, adopting a theoretical intercultural perspective, with a critical view of the processes, curriculum and individuals. As a comparative analysis device of this research, the reference documents in the Action Plan of World Program of Education in Human Rights as well as the curricular and methodological proposal of the Inter-American Institute of Human Rights - IIDH and national policy documents were collated. Research results indicate a coeherence between EDH principles and Marista Network of Basic Education's educatives principles, and the need of progress in their socio-educational practices present in pastoral, cultural and sports activities, that experiences the dimension of education in human rights as a systematic and multidimensional process.